Honoring Student “Voice” in Investigating Student Identity Development in a Narrative Study: A Methodological and Analytical Example - Lees, Deborah; Van Zyl, André (Qualitative Sociology Review, 2022)
Multiple, interrelated narrative methods were employed in a doctoral study purposed to investigate the student identity development of seven first-year participants. This approach provided them with multiple opportunities to convey their unique first-year experiences and revealed rich understandings of how they constructed their identities at a private higher education provider in Johannesburg, South Africa. The purpose of this article is to demonstrate that fostering the trust of participants ensured the formation of rich biographical narrative portraits through multiple narrative-type collection methods and forms of analyses, resulting in rich tapestries of personal experience, which were constitutive of their identity formation. Each participant’s narratives revealed their particularities, complexities, and unique experiences of their first year. Although each participant experienced their first year of study very differently, this article weaves in the first-year experiences of one person into its fabric. The narrations of Kondwani (pseudonym), a Zambian student, are used to illustrate how her voice emerged and was held in a trustful research relationship. Her case is representative of all the participants in that it is an exemplar to illustrate the richness of the individual narratives gleaned from carefully chosen methods and forms of analysis that were employed in the study.